Remote EPID-based dosimetric auditing using DVH patient dose analysis. (7th February 2023) - Greer, P B; Standen, T; David, R; Miri, N; Bobrowski, K; Lehmann, J; Zwan, B; Moore, A
Abstract: Objective. The aim of this work was to develop and validate a method for remote dosimetric auditing that enables dose-volume histogram parameter comparisons of measured and planned dose in the patient CT volume. Approach . The method is derived by adapting and combining a remote electronic portal imaging (EPID) based auditing method (Virtual Epid based Standard Phantom Audit—VESPA) and a method to estimate 3D in-patient dose distributions from planar dosimetric measurements. The method was tested with a series of error-induced plans including monitor unit and multileaf collimator (MLC) positioning errors. A pilot audit study was conducted with eleven radiotherapy centres. IMRT plans from two clinical trials, a post-prostatectomy (RAVES trial) plan and a head and neck (HPV trial) plan were utilized. Clinically relevant DVH parameters for the planned dose and estimated measured dose were compared. Main results . The method was found to reproduce the induced dose errors within 0.5% and was sensitive to MLC positioning errors as small as 0.5 mm. For the RAVES plan audit all DVH results except one were within 3% and for the HPV plan audit all DVH results were within 3% except three with a maximum difference of 3.2%. Significance . The results from the audit method produce clinically meaningful DVH metrics for the audited plan and could enable an improved understanding of a centre's radiotherapy quality.